Transformasi Politik dan Nasionalisme Indonesia Terhadap Malaysia - WARJIO WARJIO; HERI KUSMANTO (Universitas Sumatera Utara, 2010)
Indonesia nationalism evocation as the same manner as triggered by social organization and politics like Budi Utomo and Syarikat Islam has been disband but later become a strength. This happened because there are the chance equality, aspiration equality, and ideology equality. In other hand outside of Indonesia also felt this effect. The one of country that feels of this is Ma-laysia. This study focused on Indonesia nationalism effect to Malaysia nationalism evocation. Especially explain about how the process of political transformation and Indonesia nationalism to Malaysia. Based on historical approach this study has found that Indonesia nationalism and Malaysia nationalism evocation each other related. Furthermore he came to be as political identities. Political party in Malaysia like UMNO, PAS is the one of organization that has many influenced by spirit of Indonesia nationalism evocation effect. They always exist in Malaysia political configuration.Keywords: Political Transformation, Nationalism revival.